Strategi Komunikasi Dakwah Gus Bahru Zamzami di Akun Instagram @bahruzamzami - Al Aliby, Melky Rama; Jayanto, Arik Dwi; Sari, Dewi Yunita (IAIN PONOROGO, 2025)
The digital era has transformed the landscape of da'wah communication, where social media such as Instagram has become a strategic space for preachers to convey religious messages more interactively and massively. Gus Bahru Zamzami is present as one of the young cleric figures who actively utilizes the Instagram platform (@bahruzamzami) to convey religious teachings, and influence the behavior of audiences, especially the younger generation. This study aims to analyze Gus Bahru Zamzami's persuasive communication strategy on Instagram using the Theory of Planned Behavior framework, which focuses on its three main components: attitude toward behavior, subjective norms, and perceived behavioral control. This study uses a qualitative approach with a netnography method, where primary data is obtained from observations of all content on the @bahruzamzami Instagram account, including feeds, stories, and reels. The unit of analysis is each post containing a persuasive message to invite, change, or strengthen the attitudes and behavior of followers. The data analysis technique is carried out through qualitative content analysis. The research results show that Gus Bahru's communication strategy successfully integrated the three pillars of the TPB holistically and contextually. In shaping attitudes, he linked expected behaviors with instrumental benefits and religio-cultural values. In the subjective norm aspect, religious authority such as sacred texts, the wisdom of scholars, and the vision of Islam as rahmatan lil 'alamin (blessing for all the universe) was used to create positive social pressure. Meanwhile, perceived behavioral control was realized through the presentation of applicable operational models, such as living examples, which facilitated the audience's internalization of these values.